A History of Lithic Technological Studies in the Paleoindian Archaeology in the United States of America - Potter, Bethany; Sellet, Frederic (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
Lithic analyses have long been at the core of Paleoindian studies in the United States, but despite crucial changes in method and orientation, the earliest typological approaches continue to exert a strong influence on archaeologists’ understanding of Paleoindian assemblages. This chapter argues against these normative approaches by advocating in favor of dynamic perspectives on human behavior. It does so by outlining the historical contributions of technological studies to the discipline, from the early European influences to the more holistic frameworks used today. Our discussion underscores three fundamental phases of development, starting with key experimental work on the Folsom point in the mid-twentieth century. This led to an increased focus on the technological aspects of tool production and use. The second phase is heavily influenced by the development of processual archaeology, which had a profound effect on the conceptualization of lithic assemblages. It generated a wealth of systems-oriented approaches focused on the economy of lithic raw materials. Finally, and most recently, the boom in cultural ecological studies has again reshaped this landscape by creating modes of analysis that understand lithic technology as a strategic adaptation rather than a cultural fossil. To integrate these developments within the broader field of Paleoindian studies, we consider seminal papers and their role in heralding new orientations, alongside data illustrating these trends in publication.